Modified binder, dry electrode and preparation method thereof, and secondary battery
By setting up a cladding layer and plasma treatment on the surface of the adhesive core, combined with the dry electrode process, the adhesive stability and environmental problems are solved, the battery performance and safety are improved, and the process flow is simplified.
Patent Information
- Application Number
- CN202311156032.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-09-07
AI Technical Summary
In the existing battery electrode preparation process, the adhesive is unstable during the preparation process, resulting in poor performance. Especially in the dry electrode process, the adhesive stability requirements are high under the action of shear force during fibrosis, and traditional The use of organic solvents in the process increases costs and environmental problems.
Using a modified adhesive, the coating layer is prepared by setting a coating layer on the surface of the adhesive core by atomic layer deposition method, and the adhesive is subjected to plasma treatment to improve stability, reduce side reactions, combined with dry method The electrode process is used without solvents, simplifying the process flow.
Improves the stability of the binder and battery safety performance, simplifies the preparation process, reduces environmental impact, and improves the energy density and cycling performance of the battery.
Smart Images

Figure CN117199370B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and relates to a modified binder, a dry electrode, a preparation method thereof, and a secondary battery. Background Art
[0002] In the front stage of battery electrode production, the traditional wet electrode process is generally used. The wet electrode process requires the preparation of slurry. The common method is: the active material, conductive agent, binder and solvent are mixed evenly to prepare a slurry of a certain viscosity; then the slurry is coated on a metal foil of a certain thickness, dried, and made into battery electrodes for the subsequent production of battery cells.
[0003] However, the wet electrode preparation process requires steps such as homogenization and drying, with a long process flow and cumbersome operation. In addition, the use of organic solvents may increase the preparation cost and may also cause environmental problems. The dry preparation process without the use of solvents has attracted more and more attention from researchers. For example, CN112289976A discloses a method for preparing a positive electrode using a dry electrode process, and the preparation method includes: 1) mixing a fiberizable polymer powder, a carbon-coated positive electrode active material and a conductive carbon material, and then drawing the fiberizable polymer powder under the action of shear force to form fibers to obtain a mixture; 2) hot pressing the mixture on the current collector to a preset thickness to obtain the positive electrode material layer. The positive electrode material layer is compounded with the current collector to obtain a positive electrode. For example, CN115275110A discloses a positive electrode dry film preparation process and a positive electrode dry film, the preparation method of which includes: stirring and mixing the raw materials, mixing and stirring the ternary positive electrode material, SP, and PTFE to obtain a premix; fiberizing the premix, fiberizing the premix to obtain a fiberized mixture; baking the mixture, baking the fiberized mixture to obtain a marshmallow-like mixture; kneading the mixture, kneading the marshmallow-like mixture; film forming the mixture, repeatedly folding the mixture, and performing multiple rolling processes to obtain a thicker film; thinning the film, thinning the thicker film to obtain a positive electrode film.
[0004] However, it should be noted that regardless of whether it is a wet electrode process or a dry electrode process, the binder must go through steps such as mixing during the preparation process. During the preparation process, the performance may deteriorate due to the instability of the binder. Especially in the dry electrode process, the binder needs to withstand a certain shear force during the fiberization process to achieve fiberization, so higher requirements are placed on its stability.
[0005] Therefore, it is necessary to provide a method for improving a binder and a modified binder so that the binder can be applied to a battery to better improve the performance of the battery. Summary of the invention
[0006] In view of the above problems existing in the prior art, the object of the present invention is to provide a modified binder, a dry electrode and a preparation method thereof, and a secondary battery.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a modified binder, comprising a binder core and a coating layer coated on the surface of the binder core.
[0009] The present invention can ensure that the binder maintains good stability during use (for example, using the binder to prepare a dry electrode), and overcomes the problem of the binder failing during the preparation process by providing a coating layer on the surface of the binder core. At the same time, it can also reduce the battery performance failure caused by the side reaction of the binder with other substances in the electrochemical reaction, thereby achieving the purpose of stabilizing the binder and improving the safety performance of the battery.
[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0011] Preferably, the coating layer includes at least one of a carbon layer and an oxide layer.
[0012] Preferably, the oxide includes at least one of Al2O3, silicon oxide, niobium oxide and titanium dioxide.
[0013] Preferably, based on the mass of the binder core being 100%, the content of the coating layer is 0.1%-0.2%, for example, 0.1%, 0.12%, 0.15%, 0.17%, 0.18% or 0.2%.
[0014] Preferably, the coating layer is prepared by atomic layer deposition.
[0015] Preferably, the temperature of the atomic layer deposition is 60°C to 250°C, for example, 60°C, 70°C, 80°C, 100°C, 120°C, 130°C, 150°C, 160°C, 180°C, 200°C, 210°C, 220°C, 230°C or 250°C, etc.
[0016] Preferably, the atomic layer deposition is performed 20 to 100 times, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 times.
[0017] Preferably, the binder core is a fibrillatable binder.
[0018] Preferably, the binder core comprises polytetrafluoroethylene (PTFE).
[0019] Preferably, the adhesive core is an adhesive treated by plasma. The present invention can passivate overactive groups on the adhesive surface and clean the adhesive surface by subjecting the adhesive to plasma treatment.
[0020] Preferably, the gas used for the plasma treatment includes but is not limited to any one of argon, helium, oxygen, nitrogen or argon-hydrogen mixed gas, wherein the argon-hydrogen mixed gas refers to a mixed gas of argon and hydrogen.
[0021] Preferably, the vacuum degree of the plasma treatment is less than 10 -3 kPa.
[0022] Preferably, the plasma treatment time is 10s to 900s, for example, 10s, 20s, 30s, 40s, 50s, 60s, 80s, 100s, 120s, 150s, 170s, 200s, 220s, 240s, 280s, 300s, 330s, 360s, 400s, 450s, 500s, 550s, 600s, 650s, 700s, 750s, 800s, 850s or 900s, etc., preferably 10s to 600s.
[0023] In a second aspect, the present invention provides a method for preparing the modified binder according to the first aspect, the preparation method comprising the following steps:
[0024] The coating layer is deposited on the surface of the binder core by atomic layer deposition.
[0025] Preferably, the coating layer is Al2O3, and the raw material used for the atomic layer deposition is an Al2O3 precursor, and the Al2O3 precursor includes at least one of tripropylaluminum, trimethylaluminum, diisobutylaluminum hydride, diethylaluminum chloride, diisobutylaluminum hydride, aluminum tert-butoxide, aluminum isopropoxide, aluminum triethanolate, aluminum acetylacetonate and aluminum subacetate.
[0026] Preferably, the coating layer is a silicon oxide layer, and the raw material used for the atomic layer deposition is a silicon oxide precursor, and the silicon oxide precursor includes at least one of tetraethyl orthosilicate, dimethylsiloxane, dichlorosilane, disilane, hexamethyldioxysilane, octamethylcyclotetrasiloxane, tetramethylsilane, hexachlorodisilane, bis(tert-butylamino)silane, bis(diethylamino)silane, tris(dimethylamino)silane and trisilylamine.
[0027] Preferably, the coating layer is a niobium oxide layer, the raw material used in the atomic layer deposition is a niobium oxide precursor, and the niobium oxide precursor includes at least one of niobium pentachloride and niobium oxalate.
[0028] Preferably, the coating layer is a titanium oxide layer, the raw material used for the atomic layer deposition is a titanium oxide precursor, and the titanium dioxide precursor includes at least one of tetrakis(dimethylamino)titanium, tetrabutyl titanate, isopropyl titanate, titanyl sulfate, TiCl4 and TiCl3.
[0029] Preferably, the coating layer is a carbon layer, the raw material used in the atomic layer deposition is a precursor of the carbon layer, and the precursor of the carbon layer includes at least one of a carbohydrate, an organic carbon source and a hydrocarbon.
[0030] Preferably, the carbohydrate can be selected from any one of carbohydrates such as sucrose, glucose, fructose, ribose, starch, oil, protein, cellulose, etc. The organic carbon source can be selected from any one of organic carbon sources such as polyacrylonitrile, asphalt, polyvinyl alcohol, polyethylene glycol, polyfurfuryl alcohol, polyepichlorohydrin, polystyrene, phenolic resin, epoxy resin, acrylic resin, vinyl ester resin, melamine-formaldehyde resin, unsaturated polyester resin, etc. The hydrocarbon can be selected from any one of hydrocarbons such as methane, ethane, ethylene, acetylene, n-hexane, cyclohexane, benzene, toluene, xylene, methanol, ethanol, acetone, carbon monoxide, etc.
[0031] Preferably, the method for preparing the modified binder further comprises plasma treating the binder core before deposition.
[0032] Preferably, the plasma treatment includes: placing the adhesive core in a cavity of a plasma device, and when a preset vacuum degree is reached, treating with argon or helium for 10s to 900s, for example, 10s, 20s, 30s, 40s, 50s, 60s, 80s, 100s, 120s, 150s, 170s, 200s, 220s, 240s, 280s, 300s, 330s, 360s, 400s, 450s, 500s, 550s, 600s, 650s, 700s, 750s, 800s, 850s or 900s, etc.
[0033] In one embodiment, the preset vacuum degree is less than 10 -3 kPa;
[0034] In a third aspect, the present invention provides a dry electrode, comprising a current collector and an electrode film arranged on the surface of the current collector, wherein the electrode film comprises an active material, a conductive agent and a binder, wherein the binder comprises the modified binder described in the first aspect, and the binder comprises a fiberizable binder.
[0035] In the present invention, when the modified binder described in the first aspect is a fiberizable binder, the binder in the dry-process self-supporting electrode membrane can be selected in whole or in part from the modified binder described in the first aspect; when the modified binder described in the first aspect is not fiberizable, the binder in the dry-process self-supporting electrode membrane should also include other fiberizable binders commonly used in the art.
[0036] Preferably, the current collector includes an organic film and metal layers located on both sides of the organic film. The current collector has a sandwich structure, and the use of the organic film can reduce the weight of the current collector. Compared with traditional foil materials, the current collector of the present invention has the characteristics of light weight and strong safety, which is conducive to improving the energy density of the battery.
[0037] Preferably, the organic film comprises at least one of polyethylene terephthalate (PET), polymethyl methacrylate (PMMA) and acrylonitrile-butadiene-styrene copolymer (ABS);
[0038] Preferably, the metal layers on both sides of the organic film are of the same or different types, and are independently selected from at least one of an aluminum layer, a nickel layer, and a copper layer. Here, "independently selected" means that the metal layers on both sides are selected independently of each other and do not affect each other.
[0039] In one embodiment, the current collector is a composite aluminum foil having a sandwich structure, wherein the composite aluminum foil includes an organic film and metal layers located on both sides of the organic film, wherein the organic film is a PET layer or a PMMA layer, and the metal layers on both sides are aluminum layers.
[0040] Preferably, the surface of the current collector is also coated with a modified layer.
[0041] Preferably, the modified layer includes at least one of a carbon layer and a glue layer.
[0042] In the present invention, the modified layer can be a single carbon layer, a single glue layer, or a composite layer of a carbon layer and a glue layer. By providing a glue layer on the surface of the current collector, it is beneficial to subsequently hot-roll the current collector and the dry-process self-supporting electrode film to form a dry-process electrode sheet, thereby improving the adhesion between the two and improving the safety of the battery made of the dry-process electrode.
[0043] In the present invention, the provision of the carbon layer can improve the conductivity of the current collector while improving the bonding between the current collector and the electrode layer.
[0044] Preferably, the modified layer is a carbon layer.
[0045] Preferably, the modified layer comprises a carbon layer and a glue layer stacked in sequence, the carbon layer is close to the organic film, and the glue layer is far away from the organic film.
[0046] In one embodiment, the glue layer is a PVDF layer.
[0047] Preferably, the thickness of the carbon layer is 0.5 μm to 2 μm. Within this range, the improvement of conductivity and bonding can be better balanced, and the proportion of active materials in the battery can be higher.
[0048] Preferably, the thickness of the glue layer is 1 μm to 3 μm. Within this range, the bonding performance between the current collector and the electrode layer can be better improved, and the battery prepared using the glue layer can have good electrochemical performance.
[0049] Preferably, the current collector is a current collector that has been subjected to corona treatment. The corona treatment can clean the surface of the current collector, avoid side reactions caused by impurities, and improve the bonding between the current collector and the electrode layer.
[0050] In one embodiment, a carbon layer is disposed on the surface of the current collector as a modified layer, and then a corona treatment is performed.
[0051] Preferably, based on the total mass of the active material, the conductive agent and the binder as 100%, the mass ratio of the active material, the conductive agent and the binder is (85% to 99%): (0.5% to 10%): (0.5% to 5%), wherein the mass content of the active material "85% to 99%" can be, for example, 85%, 86%, 87%, 88%, 90%, 91%, 92%, 94%, 95%, 96%, 97% or 99%, and the mass content of the conductive agent "85% to 99%" can be, for example, 85%, 86%, 87%, 88%, 90%, 91%, 92%, 94%, 95%, 96%, 97% or 99%, etc. The mass content of "0.5% to 10%" can be, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 10%, etc. The mass content of the binder of "0.5% to 5%" can be, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc. Those skilled in the art can adjust the above content ratio according to the capacity requirements of the electrode.
[0052] In the present invention, the dry self-supporting electrode film can be a positive electrode or a negative electrode. Those skilled in the art can prepare the corresponding electrode film as needed. It can be understood that for the positive electrode, the corresponding active material is the positive electrode active material, and for the negative electrode, the corresponding active material is the negative electrode active material.
[0053] The present invention does not limit the specific types of active materials, conductive agents and binders. Those skilled in the art can select them according to their needs. For example and not limitation, the dry self-supporting electrode film is used as the positive electrode for illustration. The positive electrode active material can be at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium manganate, etc. The conductive agent can be at least one of Super P, acetylene black, Ketjen black, graphene and carbon nanotubes. The binder can be at least one of polytetrafluoroethylene (PFEF) or polyvinylidene fluoride (PVDF).
[0054] In a fourth aspect, the present invention provides a method for preparing a dry electrode as described in the third aspect, the method comprising the following steps:
[0055] The active material, the conductive agent and the binder are mixed by dry process, and then hot pressed to obtain a dry process self-supporting electrode film, and the current collector and the dry process self-supporting electrode film are stacked and then hot pressed to obtain a dry process electrode;
[0056] or,
[0057] After the active material, conductive agent and binder are dry-mixed, the resulting mixture is sprayed onto the current collector and hot-pressed to obtain a dry electrode.
[0058] The present invention adopts a dry electrode process to prepare a dry electrode. No solvent is used in the preparation process, which is environmentally friendly, safe, simple, easy to operate, and suitable for industrial production. At the same time, the dry electrode process can prepare thick electrodes, which are thicker than the wet electrode process, which is beneficial to improving the energy density of the battery.
[0059] Preferably, the dry mixing is performed in the following manner: after the active material and the conductive agent are mixed, a binder is added and stirred to make the binder which can be fiberized undergo fiberization to obtain a material.
[0060] Preferably, after the active material and the conductive agent are mixed, low-speed stirring and high-speed stirring are sequentially performed, the rotation speed of the low-speed stirring is 200rpm to 500rpm, such as 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm or 500rpm, etc., and the rotation speed of the high-speed stirring is 1000rpm to 4000rpm, such as 1000rpm, 1250rpm, 1500rpm, 1700rpm, 1800rpm, 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm, 3500rpm or 4000rpm, etc. By stirring at a low speed first and then at a high speed, the uniformity of the mixture can be effectively improved.
[0061] Preferably, the high-speed stirring is divided into two steps, the first step of high-speed stirring has a rotation speed of 1000rpm to 2500rpm, such as 1000rpm, 1250rpm, 1500rpm, 1700rpm, 1800rpm, 2000rpm, 2200rpm, 2400rpm or 2500rpm, etc., and the second step of high-speed stirring has a rotation speed of 3000rpm to 4000rpm, such as 3000rpm, 3200rpm, 3400rpm, 3600rpm, 3800rpm or 4000rpm, etc. According to this scheme, high-speed stirring can further improve the uniformity of the mixture.
[0062] Preferably, the time for low-speed stirring is 1 min to 20 min, for example, 1 min, 2 min, 3 min, 5 min, 8 min, 10 min, 12 min, 14 min, 15 min, 17 min, 18 min or 20 min, etc.; the time for high-speed stirring is 1 min to 60 min, for example, 1 min, 2 min, 3 min, 5 min, 8 min, 10 min, 12 min, 14 min, 15 min, 17 min, 18 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.
[0063] Preferably, after adding the binder, the stirring method is: first stirring at 300 rpm to 1000 rpm, and then stirring at 3500 rpm to 5000 rpm. In this way, the mixing uniformity of the binder and other components can be ensured, and the fiberization of the binder can be ensured.
[0064] The speed of the primary stirring may be, for example, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, etc. The speed of the secondary stirring may be, for example, 3500 rpm, 3600 rpm, 3700 rpm, 3800 rpm, 4000 rpm, 4150 rpm, 4300 rpm, 4400 rpm, 4500 rpm, 4600 rpm, 4700 rpm, 4800 rpm or 5000 rpm, etc.
[0065] Preferably, the stirring time is 1 min to 20 min, for example, 1 min, 2 min, 3 min, 5 min, 8 min, 10 min, 12 min, 14 min, 15 min, 17 min, 18 min or 20 min, etc.
[0066] Preferably, the secondary stirring time is 3 min to 5 min, such as 3 min, 4 min or 5 min.
[0067] Preferably, before the dry self-supporting electrode film is stacked on the current collector, the surface of the dry self-supporting electrode film opposite to the current collector is coated with glue. Such an arrangement is conducive to hot rolling the two to form a dry electrode, improve the adhesion between the two, and improve the safety of the battery made using the dry electrode.
[0068] Preferably, the temperature of the hot pressing is 80°C to 120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.
[0069] Preferably, the hot pressing is hot roller pressing or flat plate hot pressing.
[0070] In the present invention, the hot pressing involved in different steps, the selected temperature or the hot pressing method can be the same or different, and those skilled in the art can select according to needs.
[0071] In one embodiment, a method for preparing a dry electrode is provided, and the process flow chart thereof is shown in Figure 1 , including the following steps:
[0072] S1. After the core of the binder is subjected to plasma treatment, a coating layer is deposited on the surface of the core of the binder by an atomic layer deposition method to obtain a modified binder. The structural schematic diagram of the modified binder is as shown in Figure 2 As shown;
[0073] S2, dry-mixing the active material, the conductive agent and the modified binder, and hot-pressing to obtain a dry self-supporting electrode film;
[0074] S3, stacking the current collector and the dry process self-supporting electrode film and hot pressing them to obtain a dry process electrode.
[0075] Figure 3 The schematic diagram of the structure of each component in the material obtained after dry mixing is shown, wherein 1 is the modified binder after fiberization, 2 is the active material, and 3 is the conductive agent.
[0076] In a fifth aspect, the present invention provides a secondary battery, the secondary battery comprising the dry electrode according to the fourth aspect. The dry electrode of the present invention is applied to a battery, which is beneficial to improving the safety performance of the battery.
[0077] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0078] Compared with the prior art, the present invention has the following beneficial effects:
[0079] (1) The present invention provides a coating layer on the surface of the binder core, thereby ensuring that the binder maintains good stability during use (for example, using the binder to prepare a dry electrode), thereby overcoming the problem of the binder failing during the preparation process. At the same time, it can also reduce the battery performance failure caused by the side reaction of the binder with other substances in the electrochemical reaction, thereby achieving the purpose of stabilizing the binder and facilitating improving the safety performance of the battery.
[0080] (2) The present invention adopts a dry electrode process to prepare a dry electrode. No solvent is used in the preparation process, which is environmentally friendly and safe. The preparation process is simple and easy to operate, and is suitable for industrial production.
[0081] (3) Compared with traditional foils, the current collector of the present invention has the characteristics of light weight and high safety, which is conducive to improving the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 It is a process flow chart of a method for preparing a dry electrode provided in one embodiment of the present invention.
[0083] Figure 2 1 is a schematic diagram of the structure of a modified binder, wherein 11 is a binder core and 12 is a coating layer.
[0084] Figure 3 It is a schematic diagram of the structure of each component in the material obtained after dry mixing. DETAILED DESCRIPTION
[0085] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0086] In the embodiment of the present invention, a dry-process positive electrode is taken as an example for description, but it is not limited thereto, and a dry-process negative electrode is also applicable to the present invention.
[0087] In the embodiment of the present invention, lithium iron phosphate is used as the active material and Super P is used as the conductive agent in the dry positive electrode, but it is not limited thereto. Other types of positive electrode active materials and conductive agents are also applicable to the present invention. Similarly, the mass ratio of the positive electrode active material, the conductive agent and the binder can be adaptively adjusted as needed, and the present invention does not make specific limitations.
[0088] Example A1
[0089] A modified adhesive comprises an adhesive core and a coating layer coated on the surface of the adhesive core, wherein the adhesive core is polytetrafluoroethylene (PTFE) and the coating layer is Al2O3. Based on the mass of the adhesive core being 100%, the content of the coating layer is 0.10%.
[0090] The preparation method of the modified binder comprises the following steps:
[0091] (1) Place the binder PTFE in the plasma equipment chamber and wait until the vacuum degree reaches 10 -4 kPa, treated with argon for 120 s;
[0092] (2) The treated binder is then deposited in an atomic layer deposition (ALD) reaction chamber, using tripropylaluminum as a precursor of Al2O3, with a deposition temperature of 100°C and a deposition number of 50 times to obtain a modified binder.
[0093] Example A2
[0094] A modified adhesive comprises an adhesive core and a coating layer coated on the surface of the adhesive core, wherein the adhesive core is polytetrafluoroethylene (PTFE) and the coating layer is Al2O3. Based on the mass of the adhesive core being 100%, the content of the coating layer is 0.15%.
[0095] The preparation method of the modified binder comprises the following steps:
[0096] (1) Place the binder PTFE in the plasma equipment chamber and wait until the vacuum reaches 5×10 -4 kPa, treated with helium for 500s;
[0097] (2) The treated binder is then deposited in an atomic layer deposition (ALD) reaction chamber, using trimethylaluminum as a precursor of Al2O3, with a deposition temperature of 150°C and a deposition number of 30 times to obtain a modified binder.
[0098] Example A3
[0099] A modified adhesive comprises an adhesive core and a coating layer coated on the surface of the adhesive core, wherein the adhesive core is polytetrafluoroethylene (PTFE) and the coating layer is Al2O3. Based on the mass of the adhesive core being 100%, the content of the coating layer is 0.20%.
[0100] The preparation method of the modified binder comprises the following steps:
[0101] (1) Place the binder PTFE in the plasma equipment chamber and wait until the vacuum degree reaches 10 -5 kPa, treated with nitrogen for 700s;
[0102] (2) The treated binder is then deposited in an atomic layer deposition (ALD) reaction chamber, using diisobutylaluminum hydride as a precursor of Al2O3, with a deposition temperature of 200°C and a deposition number of 80 times to obtain a modified binder.
[0103] Example A4
[0104] A modified binder, the preparation method of which is different from that of Example A1 only in that step (1) is not performed, that is, plasma treatment is not performed.
[0105] Example A5
[0106] A modified binder, which differs from Example A1 only in that the content of the coating layer is 0.05%.
[0107] Example A6
[0108] A modified binder, which differs from Example A1 only in that the content of the coating layer is 0.25%.
[0109] Example A7
[0110] A modified binder, which differs from Example A1 only in that the coating layer is a carbon layer, and the content of the coating layer is the same as that of Example A1.
[0111] The modified binder is prepared by the following method, comprising the following steps:
[0112] (1) Place the binder PTFE in the plasma equipment chamber and wait until the vacuum degree reaches 10 -4 kPa, treated with argon for 120 s;
[0113] (2) The treated adhesive is then deposited in an atomic layer deposition (ALD) reaction chamber using acetylene as a precursor, at a deposition temperature of 500° C., for 27 deposition times, to obtain a modified adhesive.
[0114] Comparative Example A1
[0115] A binder: the binder of this comparative example is PTFE which has not been subjected to any treatment.
[0116] Preparation Example 1
[0117] A current collector is a composite aluminum foil with a sandwich structure, comprising a PET layer and aluminum layers arranged on both side surfaces of the PET layer, the thickness of the PET layer is 6 μm, and the thickness of the aluminum layers on both side surfaces is 4 μm.
[0118] Preparation Example 2
[0119] A current collector is a composite aluminum foil with a sandwich structure, comprising a PMMA layer and aluminum layers arranged on both side surfaces of the PMMA layer, the PMMA layer is 10 μm thick, and the aluminum layers on both side surfaces are 2 μm thick.
[0120] Preparation Example 3
[0121] A current collector, which is different from Preparation Example 1 only in that the outer surfaces of the aluminum layers on both sides are further provided with a carbon layer, and the thickness of the carbon layer is 1 μm.
[0122] Preparation Example 4
[0123] A current collector, which is different from Preparation Example 3 only in that the current collector having a carbon layer is subjected to corona treatment.
[0124] Preparation Example 5
[0125] A current collector, which differs from Preparation Example 1 only in that the outer surfaces of the aluminum layers on both sides are also sequentially provided with a carbon layer and a glue layer, the thickness of the carbon layer is 1 μm, and the thickness of the glue layer is 2 μm.
[0126] Preparation Comparative Example 1
[0127] A current collector, the current collector of this preparation comparative example is an aluminum foil with a thickness of 14 μm.
[0128] Example B1
[0129] A dry-process positive electrode comprises a current collector and an electrode film arranged on both sides of the current collector, wherein the electrode film comprises lithium iron phosphate, Super P and a modified binder.
[0130] The preparation method of the dry positive electrode comprises the following steps:
[0131] (1) Lithium iron phosphate (LiFePO4) is used as the positive electrode active material, Super P is used as the conductive agent, and the modified binder (Example A1) is used as the binder, wherein the mass ratio of lithium iron phosphate, Super P and the binder is 96:1:3. Lithium iron phosphate and the conductive agent are added to a high-speed mixer, first stirred at 300 rpm for 5 minutes, then stirred at 2000 rpm for 2 minutes, then stirred at 4000 rpm for 15 minutes, and then the binder is added, stirred at 300 rpm for 10 minutes, and then stirred at 4000 rpm for 5 minutes to obtain a flocculent and uniform mixture.
[0132] (2) The above mixture was added into a roller press and hot roller pressed at 120° C. to obtain a self-supporting electrode film.
[0133] (3) The self-supporting electrode film and the current collector (preparation example 1, thickness of 14 μm) are stacked and then hot rolled, wherein the self-supporting electrode film is stacked on both side surfaces of the current collector respectively, and the temperature of hot rolling is 100° C. to obtain a positive electrode sheet.
[0134] Examples B2-B7
[0135] A dry-process positive electrode, the preparation method of which is different from that of Example B1 only in that the binder is replaced by the modified binder prepared in Example A1 with the modified binder prepared in Examples A2-A7, respectively, and the other preparation methods and parameters are the same as those of Example B1.
[0136] Comparative Example B1
[0137] A dry-process positive electrode, the preparation method of which is different from that of Example B1 only in that the binder uses PTFE of Comparative Example A1 to replace the modified binder prepared in Example A1, and other preparation methods and parameters are the same as those of Example B1.
[0138] Examples B8-B11
[0139] A dry-process positive electrode, the preparation method of which is different from that of Example B1 only in that the current collectors prepared in Preparation Examples 2-5 are used to replace the current collectors prepared in Preparation Example 1, and other preparation methods and parameters are the same as those of Example B1.
[0140] Comparative Example B2
[0141] A dry-process positive electrode, the preparation method of which is different from that of Example B1 only in that the current collector uses the aluminum foil prepared in Comparative Example 1 to replace the current collector prepared in Preparation Example 1, and other preparation methods and parameters are the same as those of Example B1.
[0142] Example B12
[0143] A dry-process positive electrode comprises a current collector and an electrode film arranged on both sides of the current collector, wherein the electrode film comprises lithium iron phosphate, Super P and a modified binder.
[0144] The preparation method of the dry positive electrode comprises the following steps:
[0145] (1) Lithium iron phosphate (LiFePO4) is used as the positive electrode active material, Super P is used as the conductive agent, and the modified binder (Example A1) is used as the binder, wherein the mass ratio of lithium iron phosphate, Super P and the binder is 96:1:3. Lithium iron phosphate and the conductive agent are added to a high-speed mixer, first stirred at a low speed of 250 rpm for 15 minutes, then stirred at a high speed of 1000 rpm for 30 minutes in the first step, and then stirred at a high speed of 4000 rpm for 10 minutes in the second step, and then the binder is added, stirred at 500 rpm for 5 minutes, and then stirred at 4500 rpm for 3 minutes to obtain a flocculent and uniform mixture.
[0146] (2) The above mixture was added into a roller press and hot roller pressed at 120° C. to obtain a self-supporting electrode film.
[0147] (3) A sandwich-structured composite aluminum foil is used as a current collector. The composite aluminum foil includes an ABS layer and aluminum layers arranged on both sides of the ABS layer. The thickness of the ABS layer is 8 μm, and the thickness of the aluminum layers on both sides is 3 μm. The self-supporting electrode film and the current collector are stacked and hot rolled at a temperature of 110°C to obtain a positive electrode sheet.
[0148] Application Example 1
[0149] A lithium ion battery with a capacity of 280Ah comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the separator is located between the positive electrode and the negative electrode, and the positive electrode adopts the dry-process positive electrode prepared in Example B1.
[0150] The preparation method of a lithium-ion battery comprises:
[0151] Negative electrode preparation:
[0152] According to the mass ratio of graphite: Super P: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1.6:1.4:2, graphite, Super P, CMC and SBR are added into solvent N-methyl pyrrolidone and mixed evenly to obtain negative electrode slurry, and the negative electrode slurry is coated on copper foil, and rolled after drying to obtain a negative electrode;
[0153] The thickness of the separator was 13 μm.
[0154] The composition of the electrolyte is as follows: ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) volume ratio = 1:1:1, the concentration of lithium hexafluorophosphate is 1 mol / L, and the mass content of vinylene carbonate is 3%.
[0155] The negative electrode, separator and positive electrode are stacked in the order of negative electrode, separator, positive electrode, separator, negative electrode, separator, ..., positive electrode, separator, negative electrode. After stacking, they are wound to obtain a core, and electrolyte is injected into the core to obtain a lithium-ion battery after formation.
[0156] Application Example 2-7
[0157] A lithium ion battery, which differs from Application Example 1 only in that the positive electrode adopts the dry-process positive electrode prepared by Examples B2-B7 to replace the dry-process positive electrode prepared by Example B1, and other preparation methods and parameters are the same as those of Application Example 1.
[0158] Application Comparative Example 1
[0159] A lithium ion battery, which differs from Application Example 1 only in that the positive electrode adopts the dry-process positive electrode prepared in Comparative Example B1 to replace the dry-process positive electrode prepared in Example B1, and other preparation methods and parameters are the same as those in Application Example 1.
[0160] Application Examples 8-11
[0161] A lithium ion battery, which differs from Application Example 1 only in that the positive electrode adopts the dry-process positive electrode prepared in Examples B8-B11 to replace the dry-process positive electrode prepared in Example B1, and other preparation methods and parameters are the same as those in Application Example 1.
[0162] Application Comparative Example 2
[0163] A lithium ion battery, which differs from Application Example 1 only in that the positive electrode adopts the dry-process positive electrode prepared in Comparative Example B2 to replace the dry-process positive electrode prepared in Example B1, and other preparation methods and parameters are the same as those in Application Example 1.
[0164] Application Example 12
[0165] A lithium ion battery, which differs from Application Example 1 only in that the positive electrode adopts the dry-process positive electrode prepared in Example B12 to replace the dry-process positive electrode prepared in Example B1, and other preparation methods and parameters are the same as those in Application Example 1.
[0166] Performance Test:
[0167] (1) Pole thickness: Use a micrometer to measure the thickness of the pole piece.
[0168] (2) Electrode surface density: Cut the electrode into 7 mm circles and weigh the mass of the electrode as m1 (in g). Cut the current collector into the same size and weigh the mass of the current collector as m0 (in g). The area of the circle after cutting is S (in m). 2 ), calculate the surface density of the pole piece, the formula is: surface density of the pole piece = (m1-m0) / S.
[0169] (3) Peel strength: Use a peel tester to test the peel strength of the electrode.
[0170] The dry-process positive electrodes provided by Examples B1-B7 and Comparative Example B1 were tested according to the above method. The test results are shown in Table 1.
[0171] Table 1
[0172] Positive electrode thickness / μm <![CDATA[Areal density / g·m -2 > <![CDATA[Peeling strength / mN·mm -1 > Example B1 398 333.2 33.8 Example B2 398 333.2 35.5 Example B3 398 333.2 34.6 Example B4 398 333.2 31.1 Example B5 398 333.2 31.7 Example B6 398 333.2 32.3 Example B7 398 333.2 32.5 Comparative Example B1 398 333.2 30.1
[0173] It can be seen from Table 1 that the peel strength of the dry-process positive electrode can be improved by modifying the binder. In the raw materials for preparing the dry-process positive electrode of Examples B1 to B3, the binder is plasma-treated and surface-coated, and has a high peel strength. In the raw materials for preparing the dry-process positive electrode of Example B4, since the binder is not plasma-treated, the performance of the binder is affected, thereby reducing the peel strength of the dry-process positive electrode. By comparing Example B1 with Examples B5-B6, it can be seen that when the content of the coating layer in the binder is in the range of 0.1% to 0.2%, it is beneficial to improve the peel strength. By comparing Example B1 with Example B7, it can be seen that the binder-coated oxide is more conducive to improving the peel strength than the coated carbon layer. In the raw materials for preparing the dry-process positive electrode of Comparative Example B1, since the binder was not modified, the peel strength of the positive electrode was greatly reduced.
[0174] (4) Cyclic performance test:
[0175] Under 25℃ conditions, 1C charging, 1C discharging, and 500 cycles, the first discharge capacity is C0, the discharge capacity at the 500th cycle is C1, and the battery cycle capacity retention rate (%) = C1 / C0×100%.
[0176] The cycle performance of the lithium-ion battery provided in Example 1-7 and Comparative Example 1 according to the above method (4) was tested. The test results are shown in Table 2.
[0177] Table 2
[0178] Cycle capacity retention rate (%) Application Example 1 98.1 Application Example 2 98.7 Application Example 3 98.3 Application Example 4 97.4 Application Example 5 96.9 Application Example 6 97.2 Application Example 7 98.8 Application Comparative Example 1 96.6
[0179] As can be seen from Table 2, the present invention can improve the structural stability of the binder and thus improve the cycle performance of the battery by modifying the binder. In the batteries of Application Examples 1 to 3, the binder is plasma treated and surface coated, and the battery has a high cycle performance. In the battery of Application Example 4, since the binder has not been plasma treated, the performance of the binder is affected, thereby reducing the cycle performance of the battery. By comparing Application Example 1 with Application Examples 5-6, it can be seen that when the content of the coating layer in the binder is in the range of 0.1% to 0.2%, it is beneficial to improve the cycle performance of the battery. By comparing Application Example 1 with Application Example 7, it can be seen that the binder-coated carbon layer is more conducive to improving the cycle performance of the battery than the coated oxide. In the battery of Application Comparative Example 1, since the binder was not modified, the cycle performance of the battery decreased.
[0180] (5) Mass energy density test:
[0181] According to the first discharge capacity C0, the mass energy density is calculated, mass energy density = C0 × discharge platform / mass.
[0182] The mass energy density of the lithium-ion batteries provided by Example 1, Application Examples 8-11, Comparative Example 2 and Application Example 12 were tested according to the above method (5). The test results are shown in Table 3.
[0183] Table 3
[0184]
[0185] As shown in Table 3, the present invention uses a dry process to prepare the positive electrode and uses a sandwich structure current collector to effectively improve the mass energy density of the battery. In Comparative Example 2, since the current collector is pure aluminum foil, the mass energy density of the battery decreases.
[0186] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A modified binder, characterized in that: The modified binder comprises a binder core and a coating layer coated on the surface of the binder core; Taking the mass of the binder core as 100%, the content of the coating layer is 0.1%-0.2%; The coating layer includes at least one of a carbon layer and an oxide layer; The precursor of the carbon layer includes at least one of a carbohydrate, an organic carbon source and a hydrocarbon; The oxide comprises at least one of Al2O3, silicon oxide, niobium oxide and titanium dioxide; The coating layer is prepared by an atomic layer deposition method, and the number of depositions of the atomic layer deposition is 20 to 100 times; The binder core is a fiberizable binder; the binder core includes polytetrafluoroethylene; The adhesive core is an adhesive treated by plasma.
2. The modified binder according to claim 1, characterized in that: The temperature of the atomic layer deposition is 60°C to 250°C.
3. The modified binder according to claim 1, characterized in that: The gas used for the plasma treatment includes any one of argon, helium, oxygen or argon-hydrogen mixed gas.
4. The modified binder according to claim 1, characterized in that: The vacuum degree of the plasma treatment is less than 10 -3 kPa.
5. The modified binder according to claim 1, characterized in that: The plasma treatment time is 10s to 900s.
6. The modified binder according to claim 5, characterized in that: The plasma treatment time is 10s to 600s.
7. A method for preparing the modified binder according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The coating layer is deposited on the surface of the binder core by atomic layer deposition.
8. The preparation method according to claim 7, characterized in that: The coating layer is an Al2O3 layer, and the raw material used for the atomic layer deposition is an Al2O3 precursor, and the Al2O3 precursor includes at least one of tripropylaluminum, trimethylaluminum, diisobutylaluminum hydride, diethylaluminum monochloride, diisobutylaluminum hydride, aluminum tert-butoxide, aluminum isopropoxide, aluminum triethoxide, aluminum acetylacetonate and aluminum subacetate.
9. The preparation method according to claim 7, characterized in that: The coating layer is a silicon oxide layer, and the raw material used for the atomic layer deposition is a silicon oxide precursor, and the silicon oxide precursor includes at least one of tetraethyl orthosilicate, dimethylsiloxane, dichlorosilane, disilane, hexamethyldioxysilane, octamethylcyclotetrasiloxane, tetramethylsilane, hexachlorodisilane, bis(tert-butylamino)silane, bis(diethylamino)silane, tris(dimethylamino)silane and trisilylamine.
10. The preparation method according to claim 7, characterized in that: The coating layer is a niobium oxide layer, and the raw material used in the atomic layer deposition is a niobium oxide precursor, and the niobium oxide precursor includes at least one of niobium pentachloride and niobium oxalate.
11. The preparation method according to claim 7, characterized in that: The coating layer is a titanium dioxide layer, and the raw material used for the atomic layer deposition is a titanium dioxide precursor, which includes at least one of tetrakis(dimethylamino)titanium, tetrabutyl titanate, isopropyl titanate, titanyl sulfate, TiCl4 and TiCl3.
12. The preparation method according to claim 7, characterized in that: The coating layer is a carbon layer, and the raw material used in the atomic layer deposition is a precursor of the carbon layer.
13. The preparation method according to claim 7, characterized in that: The method for preparing the modified binder further includes plasma treating the binder core before deposition.
14. The preparation method according to claim 13, characterized in that: The plasma treatment comprises: placing the adhesive core in a cavity of a plasma device, and treating the cavity with argon or helium for 10s to 900s after reaching a preset vacuum degree.
15. A dry electrode, characterized in that: The dry electrode includes a current collector and an electrode film arranged on the surface of the current collector, the electrode film includes an active material, a conductive agent and a binder, the binder includes the modified binder described in any one of claims 1 to 6 or the modified binder prepared by the preparation method described in any one of claims 7 to 14, and the binder includes a fiberizable binder.
16. The dry electrode according to claim 15, characterized in that: The current collector includes an organic film and metal layers located on both sides of the organic film.
17. The dry electrode according to claim 16, characterized in that: The organic film includes at least one of polyethylene terephthalate, polymethyl methacrylate, and acrylonitrile-butadiene-styrene copolymer.
18. The dry electrode according to claim 16, characterized in that: The thickness of the organic film is 5 μm to 10 μm.
19. The dry electrode according to claim 16, characterized in that: The metal layers on both sides of the organic film are of the same or different types and are independently selected from at least one of an aluminum layer, a nickel layer and a copper layer.
20. The dry electrode according to claim 16, characterized in that: The thickness of the metal layers on both sides of the organic film is independently 1 μm to 4 μm.
21. The dry electrode according to claim 15, characterized in that: The surface of the current collector is also coated with a modified layer.
22. The dry electrode according to claim 21, characterized in that: The modified layer includes at least one of a carbon layer and a glue layer.
23. The dry electrode according to claim 22, characterized in that: The modified layer is a carbon layer.
24. The dry electrode according to claim 21, characterized in that: The modified layer includes a carbon layer and a glue layer stacked in sequence, wherein the carbon layer is close to the organic film, and the glue layer is far away from the organic film.
25. The dry electrode according to claim 22, characterized in that: The thickness of the carbon layer is 0.5 μm to 2 μm.
26. The dry electrode according to claim 22, characterized in that: The thickness of the adhesive layer is 1 μm to 3 μm.
27. The dry electrode according to claim 15, characterized in that: The current collector is a current collector after corona treatment.
28. The dry electrode according to claim 15, characterized in that: Taking the total mass of the active material, the conductive agent and the binder as 100%, the mass ratio of the active material, the conductive agent and the binder is (85%~99%):(0.5%~10%):(0.5%~5%).
29. A method for preparing a dry electrode according to any one of claims 15 to 28, characterized in that: The method comprises the following steps: The active material, the conductive agent and the binder are mixed by dry process, and then hot pressed to obtain a dry process self-supporting electrode film, and the current collector and the dry process self-supporting electrode film are stacked and then hot pressed to obtain a dry process electrode; or, After the active material, conductive agent and binder are dry-mixed, the resulting mixture is sprayed onto the current collector and hot-pressed to obtain a dry electrode.
30. The preparation method according to claim 29, characterized in that: The dry mixing is carried out in the following manner: after the active material and the conductive agent are mixed, a binder is added and stirred to fiberize the binder to obtain a material.
31. The preparation method according to claim 30, characterized in that: After the active material and the conductive agent are mixed, low-speed stirring and high-speed stirring are sequentially performed, wherein the rotation speed of the low-speed stirring is 200 rpm to 500 rpm, and the rotation speed of the high-speed stirring is 1000 rpm to 4000 rpm.
32. The preparation method according to claim 31, characterized in that: The high-speed stirring is divided into two steps. The rotation speed of the first step high-speed stirring is 1000rpm~2500rpm, and the rotation speed of the second step high-speed stirring is 3000rpm~4000rpm.
33. The preparation method according to claim 31, characterized in that: The low-speed stirring time is 1 min to 20 min, and the high-speed stirring time is 1 min to 60 min.
34. The preparation method according to claim 30, characterized in that: After adding the binder, the stirring method is: first stirring at 300rpm~1000rpm, and then stirring a second time at 3500rpm~5000rpm.
35. The preparation method according to claim 34, characterized in that: The time of the first stirring is 1 min to 20 min.
36. The preparation method according to claim 34, characterized in that: The secondary stirring time is 3 min to 5 min.
37. The preparation method according to claim 29, characterized in that: Before the dry-process self-supporting electrode film is stacked on the current collector, glue is applied on the surface of the dry-process self-supporting electrode film on the side opposite to the current collector.
38. The preparation method according to claim 29, characterized in that: The temperature of the hot pressing is 80°C to 120°C.
39. The preparation method according to claim 29, characterized in that: The hot pressing is hot roller pressing or flat plate hot pressing.
40. A secondary battery, characterized in that: The secondary battery comprises the dry electrode according to any one of claims 15 to 28 or a dry electrode prepared by the preparation method according to any one of claims 29 to 39.
Citation Information
Patent Citations
Positive electrode material layer, preparation method thereof, positive plate and battery
CN112289976A
Positive electrode dry-method film forming preparation process and positive electrode dry-method diaphragm
CN115275110A
Surface modification method for polytetrafluoroethylene separation membrane
CN102773026A
Polytetrafluoroethylene-based core-shell nano composite material as well as preparation method and application thereof
CN111286047A
Core-shell binder material and preparation method thereof
CN113480695A
